Composition, electrode, and secondary battery
Patent Information
- Application Number
- KR1020247026878
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-17
- Filing Date
- 2023-01-06
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2043-01-06
Smart Images

Figure 112024086967848-PCT00001 
Figure 112024086967848-PCT00002 
Figure 112024086967848-PCT00003
Abstract
Description
Technology Field
[0001] The present disclosure relates to a composition, an electrode, and a secondary battery. Background Technology
[0002] An electrode equipped with an electrochemical device such as a lithium-ion battery can be formed, for example, by dissolving an electrode material and a binder in a solvent and applying the resulting composition to a current collector.
[0003] As such a composition, Patent Document 1 describes a composition for an electrochemical device comprising a single layer carbon nanotube, a binder, and a solvent, wherein the binder comprises a fluorine-containing copolymer containing vinylidene fluoride units and fluorinated monomer units (excluding vinylidene fluoride units), and the content of vinylidene fluoride units in the fluorine-containing copolymer is 50.0 mol% or more relative to the total monomer units. Prior art literature
[0004] International Publication No. 2021 / 002369 The problem to be solved
[0005] The present disclosure aims to provide a composition that can obtain a battery having excellent output characteristics, cycle characteristics, and 60°C storage characteristics, and a reduced gas generation rate after high-temperature storage. means of solving the problem
[0006] According to the present disclosure, a composition is provided comprising a single layer carbon nanotube, a binder, and a solvent represented by the general formula (1), wherein the binder comprises a fluorine-containing polymer containing vinylidene fluoride units.
[0007] General formula (1):
[0008]
[0009] (during food, R 1 , R 2 and R 3is independently an H or monovalent substituent, provided that R 1 , R 2 and R 3 The total number of carbon atoms is 6 or more, and R 1 , R 2 and R 3 At least one of them is an organic group having a carbonyl group. R 1 , R 2 and R 3 Any two may combine to form a ring.
[0010] It is preferable that the above solvent is a solvent represented by the general formula (1a).
[0011] General formula (1a):
[0012]
[0013] (during food, R 1a is a monovalent substituent, and R 2a and R 3a is, independently, an H or monovalent substituent, provided that R 1a , R 2a and R 3a The total number of carbon atoms is 5 or more. R 1a , R 2a and R 3a Any two may combine to form a ring.
[0014] It is preferable that the above solvent is at least one selected from the group consisting of a solvent represented by general formula (1b-1) and a solvent represented by general formula (1b-2).
[0015] General formula (1b-1):
[0016]
[0017] (during food, R 1b is an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, or an aminoalkyl group, and R 2b and R 3b is independently an alkyl group or an alkoxyalkyl group, and R 1b , R 2b and R3b The total number of carbon atoms is 5 or more. R 2b and R 3b is, combined with each other, R 2b and R 3b It may form a ring with the nitrogen atom to which it bonds, or it may include an oxygen atom as a constituent atom of the ring.
[0018] General formula (1b-2):
[0019]
[0020] (In the formula, ring A is a 5- or 6-won amide ring, and R 4b is an alkyl group, a cycloalkyl group, or an alkenyl group, and rings A and R 4b The total number of carbon atoms is 5 or more.)
[0021] It is preferable that the above solvent is at least one selected from the group consisting of 3-methoxy-N,N-dimethylpropanamide, N-ethyl-2-pyrrolidone, and N-butyl-2-pyrrolidone.
[0022] It is preferable that the average outer diameter of the above single-layer carbon nanotube is 2.5 nm or less.
[0023] It is preferable that the average G / D ratio of the above single-layer carbon nanotube is 2 or higher.
[0024] It is preferable that the above binder contains polyvinylidene fluoride as the fluorine-containing polymer.
[0025] It is preferable that the above binder contains, as the above fluorine-containing polymer, a fluorine-containing copolymer containing vinylidene fluoride units and monomer units other than vinylidene fluoride.
[0026] It is preferable that the other monomer be a fluorinated monomer (excluding vinylidene fluoride).
[0027] It is preferable that the other monomer is at least one selected from the group consisting of tetrafluoroethylene, chlorotrifluoroethylene, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, hexafluoropropylene, and fluoroalkyl vinyl ether.
[0028] It is preferable that the above-mentioned binder contains, as the above-mentioned fluorine-containing polymer, polyvinylidene fluoride and a fluorine-containing copolymer containing vinylidene fluoride units and monomer units other than vinylidene fluoride.
[0029] It is preferable that the mass ratio of the polyvinylidene fluoride and the fluorine-containing copolymer (polyvinylidene fluoride / fluorine-containing polymer) is 99 / 1 to 1 / 99.
[0030] The composition of the present disclosure can be used to form an electrode of an electrochemical device.
[0031] The composition of the present disclosure preferably further contains a powder electrode material (except for the single-layer carbon nanotube).
[0032] It is preferable that the above powder electrode material contains a lithium composite oxide as a positive electrode active material.
[0033] It is preferable that the above powder electrode material contains a negative electrode active material that exhibits a potential of 2.5V or less based on Li when alloyed with Li or combined with Li.
[0034] In addition, according to the present disclosure, an electrode is provided having a current collector and an electrode material layer formed by the above composition, which is provided on one or both sides of the current collector.
[0035] In addition, according to the present disclosure, a secondary battery having the above electrode is provided. Effects of the invention
[0036] According to the present disclosure, a composition can be provided that enables obtaining a battery with excellent output characteristics, cycle characteristics, and 60°C storage characteristics, and a reduced gas generation rate after high-temperature storage. Specific details for implementing the invention
[0037] Specific embodiments of the present disclosure are described in detail below, but the present disclosure is not limited to the following embodiments.
[0038] The composition of the present disclosure contains a single layer carbon nanotube, a binder, and a solvent.
[0039] Patent Document 1 describes that a secondary battery with excellent output characteristics, cycle characteristics, and 60°C storage characteristics is obtained by forming an electrode using a composition for an electrochemical device containing a single layer carbon nanotube, a specific binder, and a solvent.
[0040] Upon careful examination of means to further improve the performance of a secondary battery, it was discovered that by forming an electrode using a composition containing an extremely limited solvent, a secondary battery is obtained in which not only are the output characteristics excellent, but the cycle characteristics and 60°C storage characteristics are further improved, and the gas generation rate after high-temperature storage is reduced. Below, each component contained in the composition of the present disclosure will be described in detail.
[0041] (menstruum)
[0042] The composition of the present disclosure contains a single-layer carbon nanotube and a binder, together with a solvent represented by the general formula (1). The solvent used in the present disclosure is suitably a solvent that is liquid at 20°C.
[0043] General formula (1):
[0044]
[0045] (during food, R 1 , R 2 and R 3is independently an H or monovalent substituent, provided that R 1 , R 2 and R 3 The total number of carbon atoms is 6 or more, and R 1 , R 2 and R 3 At least one of them is an organic group having a carbonyl group. R 1 , R 2 and R 3 Any two may combine to form a ring.
[0046] R 1 , R 2 and R 3 The total number of carbon atoms is 6 or more. That is, R 1 , R 2 and R 3 For each, the type of group is selected so that the total number of carbon atoms is 6 or more. R 1 , R 2 and R 3 The upper limit of the total number of carbons is not limited, but it may be 16 or less, 14 or less, or 12 or less.
[0047] R 1 , R 2 and R 3 Al is independently H or a monovalent substituent. As a monovalent substituent, an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, an aminoalkyl group, or a cycloalkyl group is preferred.
[0048] R 1 , R 2 and R 3 At least one of them is an organic group having a carbonyl group. An acyl group is preferred as the organic group having a carbonyl group. As for the acyl group, general formula: -CO-R 4 (during food, R 4 A group represented by (which is an alkyl group having 1 to 6 carbon atoms) is preferred. When the alkyl group has 3 or more carbon atoms, it may be in a straight chain or a branched chain. R 4When the number of carbon atoms in the alkyl group is 2 or more, heteroatoms such as oxygen atoms, nitrogen atoms, or carbonyl groups may be included between the carbon-carbon atoms.
[0049] R 1 , R 2 and R 3 Any two of them may combine to form a ring. Additionally, heteroatoms such as oxygen atoms may be included as constituent atoms of the ring. It is preferable that the ring be a saturated ring. The number of elements in the ring is not particularly limited, but 5 or 6 elements are preferred. As for the ring, a pyrrolidine ring, an oxazoline ring, a piperidine ring, or a morpholine ring is preferred.
[0050] As a solvent, a solvent represented by the general formula (1a) is preferred.
[0051] General formula (1a):
[0052]
[0053] (during food, R 1a is a monovalent substituent, and R 2a and R 3a is, independently, an H or monovalent substituent, provided that R 1a , R 2a and R 3a The total number of carbon atoms is 5 or more. R 1a , R 2a and R 3a Any two may combine to form a ring.
[0054] In general formula (1a), R 1a , R 2a and R 3a The total number of carbon atoms is 5 or more. That is, R 1a , R 2a and R 3a The type of group is selected for each so that the total number of carbon atoms is 5 or more. R 1a , R 2a and R 3a The upper limit of the total number of carbons is not limited, but it may be 15 or less, 13 or less, or 11 or less.
[0055] In general formula (1a), R 1a is a monovalent substituent. As a monovalent substituent, an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, an aminoalkyl group, or a cycloalkyl group is preferred, and an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, or an aminoalkyl group is more preferred.
[0056] In general formula (1a), R 2a and R 3a is, independently, an H or monovalent substituent. R 2a and R 3a As for the monovalent substituent, independently, a monovalent substituent is preferred. As the monovalent substituent, an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, an aminoalkyl group, or a cycloalkyl group is preferred, and an alkyl group, an alkoxyalkyl group, a cycloalkyl group, or an alkenyl group is more preferred.
[0057] R 1a , R 2a and R 3a Any two may combine to form a ring. In particular, R 2a and R 3a combines, R 2a and R 3a It is preferable to form a ring together with the nitrogen atom to which it bonds. Additionally, heteroatoms such as oxygen atoms may be included as constituent atoms of the ring. It is preferable that the ring be a saturated ring. The number of elements in the ring is not particularly limited, but 5 or 6 elements are preferable. As for the ring, a pyrrolidine ring, an oxazoline ring, a piperidine ring, or a morpholine ring is preferred.
[0058] As a solvent, at least one selected from the group consisting of a solvent represented by general formula (1b-1) and a solvent represented by general formula (1b-2) is more preferable.
[0059] General formula (1b-1):
[0060]
[0061] (during food, R 1b is an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, or an aminoalkyl group, and R 2b and R 3b is independently an alkyl group or an alkoxyalkyl group, and R 1b , R 2b and R 3b The total number of carbon atoms is 5 or more. R 2b and R 3b is, combined with each other, R 2b and R 3b It may form a ring with the nitrogen atom to which it bonds, or it may include an oxygen atom as a constituent atom of the ring.
[0062] General formula (1b-2):
[0063]
[0064] (In the formula, ring A is a 5- or 6-won amide ring, and R 4b is an alkyl group, a cycloalkyl group, or an alkenyl group, and rings A and R 4b The total number of carbon atoms is 5 or more.)
[0065] In general formula (1b-1), R 1b , R 2b and R 3b The total number of carbon atoms is 5 or more. That is, R 1b , R 2b and R 3b The type of group is selected for each so that the total number of carbon atoms is 5 or more. R 1b , R 2b and R 3b The upper limit of the total number of carbons is not limited, but it may be 15 or less, 13 or less, or 11 or less.
[0066] In general formula (1b-1), R 1b is an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, or an aminoalkyl group.
[0067] R 1bAs for the alkyl group, an alkyl group having 1 to 10 carbon atoms is preferred. When the alkyl group has 3 or more carbon atoms, it may be in a straight chain or a branched chain.
[0068] R 1b As the alkoxyalkyl group of, general formula: -R 1b1 -OR 1b2 (during food, R 1b1 1 to 5 carbon alkylene groups, R 1b2 A group represented by (which is an alkyl group having 1 to 5 carbon atoms) is preferred. When the number of carbon atoms of the alkyl group and the alkylene group is 3 or more, they may be straight chains or branched chains.
[0069] R 1b As the acylalkyl group of, general formula: -R 1b3 -CO-R 1b4 (during food, R 1b3 1 to 5 carbon alkylene groups, R 1b4 A group represented by (which is an alkyl group having 1 to 5 carbon atoms) is preferred. When the number of carbon atoms of the alkyl group and the alkylene group is 3 or more, they may be straight chains or branched chains.
[0070] R 1b As for the alkenyl group, general formula: -R 1b5 -CR 1b6 =CR 1b7 (during food, R 1b5 is a single bond or an alkylene group having 1 to 5 carbon atoms, R 1b6 and R 1b7 A group represented by (independently H or an alkyl group having 1 to 5 carbon atoms) is preferred. When the number of carbon atoms in the alkyl group and the alkylene group is 3 or more, they may be straight chains or branched chains. As for the alkenyl group, a vinyl group is preferred.
[0071] R 1b The amino group of the amino group and the aminoalkyl group is a monovalent functional group obtained by removing hydrogen from ammonia, a primary or secondary amine. R 1b In the case where is an amino group, R 1bIt can form an amide bond with the carbonyl group to which it binds.
[0072] R 1b As for the amino group, general formula: -N-(R 1b8 )2(food, R 1b8 A group represented by H (or an alkyl group having 1 to 5 carbon atoms) is preferred. When the alkyl group has 3 or more carbon atoms, it may be a straight chain or a branched chain. As for the amino group, -N-(CH3)2 or -N-(C2H5)2 is preferred.
[0073] R 1b As the aminoalkyl group of, general formula: -R 1b9 -N-(R 1b8 )2(food, R 1b9 is an alkylene group having 1 to 5 carbon atoms, R 1b8 A group represented by H or an alkyl group having 1 to 5 carbon atoms is preferred. When the number of carbon atoms in the alkyl group and the alkylene group is 3 or more, they may be straight chains or branched chains.
[0074] In general formula (1b-1), R 2b and R 3b is, independently, an alkyl group or an alkoxyalkyl group.
[0075] R 2b and R 3b As for the alkyl group, an alkyl group having 1 to 10 carbon atoms is preferred. When the alkyl group has 3 or more carbon atoms, it may be in a straight chain or a branched chain.
[0076] R 2b and R 3b As the alkoxyalkyl group of, general formula: -R 2b1 -OR 2b2 (during food, R 2b1 1 to 5 carbon alkylene groups, R 2b2 A group represented by (which is an alkyl group having 1 to 5 carbon atoms) is preferred. When the number of carbon atoms of the alkyl group and the alkylene group is 3 or more, they may be straight chains or branched chains.
[0077] R 2band R 3b is, combined with each other, R 2b and R 3b A ring may be formed with a nitrogen atom bonded to it, or an oxygen atom may be included as a constituent atom of the ring. It is preferable that the ring be a saturated ring. The number of elements in the ring is not particularly limited, but 5 or 6 elements are preferable. As for the ring, a pyrrolidine ring, an oxazoline ring, a piperidine ring, or a morpholine ring is preferred.
[0078] In general formula (1b-2), rings A and R 4b The total number of carbon atoms is 5 or more. That is, rings A and R 4b The types of rings and groups are selected so that the total number of carbon atoms is 5 or more. Rings A and R 4b The upper limit of the total number of carbons is not limited, but it may be 15 or less, 13 or less, or 11 or less.
[0079] Ring A is a 5- or 6-membered amide ring. Accordingly, Ring A is composed of a carbon atom and a nitrogen atom, along with an alkylene group having 3 to 4 carbon atoms. The hydrogen atoms bonded to the carbon atoms of the alkylene groups constituting Ring A may be substituted by a substituent or may not be substituted by a substituent, but it is preferable that they are not substituted by a substituent. Examples of substituents include alkyl groups such as methyl groups.
[0080] R 4b is an alkyl group, a cycloalkyl group, or an alkenyl group.
[0081] R 4b As for the alkyl group, an alkyl group having 1 to 10 carbon atoms is preferred. When the alkyl group has 3 or more carbon atoms, it may be in a straight chain or a branched chain.
[0082] R 4b As the cycloalkyl group, a cycloalkyl group having 3 to 10 carbon atoms is preferred. As the cycloalkyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, or a cyclooctyl group is preferred.
[0083] R 4b As for the alkenyl group, general formula: -R 4b1 -CR 4b2 =CR 4b3 (during food, R 4b1 Silver is a single bond or an alkylene group having 1 to 5 carbon atoms, R 4b2 and R 4b3 A group represented independently as H or an alkyl group having 1 to 5 carbon atoms is preferred. When the number of carbon atoms in the alkyl group and the alkylene group is 3 or more, they may be straight chains or branched chains. As for the alkenyl group, a vinyl group is preferred.
[0084] As a solvent, at least one selected from the group consisting of 3-methoxy-N,N-dimethylpropanamide, N-ethyl-2-pyrrolidone (NEP), N-butyl-2-pyrrolidone (NBP), acryloylmorpholine, N-cyclohexyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, 3-butoxy-N,N-dimethylpropanamide, N,N,N',N'-tetraethylurea, N,N-dimethylacetoacetamide, N-octyl-2-pyrrolidone, and N,N-diethylacetamide is preferred.
[0085] As a solvent, at least one selected from the group consisting of 3-methoxy-N,N-dimethylpropanamide, N-ethyl-2-pyrrolidone, and N-butyl-2-pyrrolidone is more preferable.
[0086] The amount of solvent in the composition is determined by considering the coating properties on the current collector, the thin film formation properties after drying, etc. Typically, the ratio of the binder to the solvent is 0.5:99.5 to 20:80 by mass.
[0087] (Single-layer carbon nanotube)
[0088] Single-layer carbon nanotubes (SWNTs) are a special class of carbon materials known as one-dimensional materials. Single-layer carbon nanotubes contain a sheet of graphene and are rolled to form a hollow tube with a wall thickness of one atomic fraction. By having such a chemical structure and size, single-layer carbon nanotubes exhibit excellent mechanical, electrical, thermal, and optical properties. Since the composition of the present disclosure contains single-layer carbon nanotubes, by using the composition of the present disclosure, a battery with excellent output characteristics, cycle characteristics, and 60°C storage characteristics, and a reduced gas generation rate can be obtained.
[0089] The average outer diameter of the single-layer carbon nanotube is preferably 2.5 nm or less, more preferably 2.0 nm or less, even more preferably 1.8 nm or less, preferably 1.0 nm or more, more preferably 1.1 nm or more, and even more preferably 1.2 nm or more. The average outer diameter of the single-layer carbon nanotube can be obtained from the light absorption spectrum, Raman spectrum, or transmission electron microscope (TEM) image of the single-layer carbon nanotube obtained by ultraviolet-visible-near-infrared spectroscopy (UV-Vis-NIR).
[0090] The average G / D ratio measured by Raman spectroscopic analysis (wavelength 532 nm) of a single-layer carbon nanotube is preferably 2 or higher, more preferably 5 or higher, even more preferably 10 or higher, particularly preferably 30 or higher, most preferably 40 or higher, preferably 250 or lower, more preferably 220 or lower, and even more preferably 180 or lower. The G / D ratio is the ratio of the intensity of the G band to the D band of the Raman spectrum of a single-layer carbon nanotube (G / D). A higher average G / D ratio of a single-layer carbon nanotube indicates higher crystallinity of the single-layer carbon nanotube and fewer impurity carbon or defective carbon nanotubes.
[0091] The average length of the single-layer carbon nanotube is preferably 0.1 to 50 μm, more preferably 0.5 to 20 μm, and even more preferably 1 to 10 μm. The average length of the single-layer carbon nanotube can be obtained by obtaining an AFM image of the single-layer carbon nanotube using an atomic force microscope (AFM) or by obtaining a TEM image of the single-layer carbon nanotube using a transmission electron microscope (TEM), measuring the length of each single-layer carbon nanotube, and dividing the sum of the lengths by the number of measured single-layer carbon nanotubes.
[0092] The content of single-layer carbon nanotubes in the composition of the present disclosure is, preferably 0.01 to 3 mass%, more preferably 0.01 to 2 mass%, even more preferably 0.01 to 1 mass%, particularly preferably 0.1 to 0.8 mass%, and most preferably 0.2 to 0.5 mass% with respect to the mass of the composition. When the content of single-layer carbon nanotubes is within the above range, an electrode composite can be prepared in which each component is sufficiently dispersed without imparting excessive shear force to the composition, and the composition has a suitable viscosity. Accordingly, a three-dimensional network of single-layer carbon nanotubes can be sufficiently formed in the electrode material layer obtained.
[0093] (Binding agent)
[0094] The binder contained in the composition of the present disclosure contains a fluorine-containing polymer containing vinylidene fluoride (VdF) units.
[0095] As a fluorine-containing polymer, at least one type selected from the group consisting of polyvinylidene fluoride (PVdF) and fluorine-containing copolymers containing VdF units and monomer units other than VdF is preferred.
[0096] The fluorine-containing copolymer contains VdF units and monomer units other than VdF. The other monomers may be fluorinated monomers or non-fluorinated monomers.
[0097] Examples of fluorinated monomers (excluding VdF) include tetrafluoroethylene (TFE), vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropene and trans-1,3,3,3-tetrafluoropropene.
[0098] As for the fluoroalkyl vinyl ether, a fluoroalkyl vinyl ether having a fluoroalkyl group having 1 to 5 carbon atoms is preferred, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether), and perfluoro(propyl vinyl ether) is more preferred.
[0099] As for the fluorinated monomer, at least one selected from the group consisting of TFE, CTFE, 2,3,3,3-tetrafluoropropene, HFP, and fluoroalkyl vinyl ether is preferred, at least one selected from the group consisting of TFE and HFP is more preferred, and TFE is particularly preferred.
[0100] Fluorinated monomers (except VdF) may or may not have polar groups.
[0101] Examples of non-fluorinated monomers include non-fluorinated monomers that do not have polar groups, such as ethylene and propylene, and non-fluorinated monomers that have polar groups (hereinafter referred to as monomers containing polar groups).
[0102] When a non-fluorinated monomer having a polar group is used, a polar group is introduced into the fluorine-containing copolymer, thereby obtaining even better adhesion between the coating layer and the metal foil. As for the polar group, at least one selected from the group consisting of carbonyl groups, epoxy groups, hydroxyl groups, sulfonic acid groups, sulfate groups, phosphate groups, amino groups, amide groups, and alkoxy groups is preferred, at least one selected from the group consisting of carbonyl groups, epoxy groups, and hydroxyl groups is more preferred, and carbonyl groups are even more preferred. The hydroxyl group does not include a hydroxyl group that constitutes a part of the carbonyl group. In addition, the amino group is a monovalent functional group obtained by removing hydrogen from ammonia, a primary or secondary amine.
[0103] The above carbonyl group containing group is a functional group having a carbonyl group (-C(=O)-). As the above carbonyl group containing group, a group represented by the general formula -COOR (where R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group) or a carboxylic acid anhydride group is preferred, and a group represented by the general formula -COOR is more preferred. The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3. Specific examples of groups represented by the general formula -COOR include -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, -COOC2H5, etc. General formula: The group represented by -COOR is -COOH, or if it contains -COOH, -COOH may be a carboxylate such as a metal carboxylate salt or an ammonium carboxylate salt.
[0104] In addition, the carbonyl group containing the above may also be represented by the general formula: -X-COOR (where X is an atomic group with a molecular weight of 500 or less in which the main chain consists of 1 to 20 atoms, and R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group). The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3.
[0105] As the above amide group, a group represented by the general formula: -CO-NRR' (R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group) or a bond represented by the general formula: -CO-NR"- (R" represents a hydrogen atom, a substituted or unsubstituted alkyl group or a substituted or unsubstituted phenyl group) is preferred.
[0106] The above polar group-containing monomers include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; alkylidenemalonic acid esters such as dimethyl methylidenemalonicate; vinylcarboxyalkyl ethers such as vinylcarboxymethyl ether and vinylcarboxyethyl ether; carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylic acid esters such as acryloyloxyethyl succinic acid, acryloyloxypropyl succinic acid, methacryloyloxyethyl succinic acid, acryloyloxyethyl phthalic acid, and methacryloyloxyethyl phthalic acid; Monoesters of unsaturated dibasic acids such as maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, citraconic acid monoethyl ester; general formula (4):
[0107]
[0108] (during food, R 11 to R 13 Silver, independently, represents a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. R 14 represents a single bond or a hydrocarbon group having 1 to 8 carbon atoms. Y1 Monomers (4) represented as inorganic cations and / or organic cations; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; etc.
[0109] As the above polar group-containing monomer unit that can be contained in the fluorine-containing copolymer, a unit based on the monomer (4) represented by the general formula (4) is preferred.
[0110] In general formula (4), Y 1 It represents inorganic cations and / or organic cations. Examples of inorganic cations include cations such as H, Li, Na, K, Mg, Ca, Al, and Fe. Examples of organic cations include NH4 and NH3R 15 , NH2R 15 2, NHR 15 3, NR 15 4(R 15 Examples of cations include (independently representing an alkyl group having 1 to 4 carbon atoms). Y 1 As for, H, Li, Na, K, Mg, Ca, Al, and NH4 are preferred, H, Li, Na, K, Mg, Al, and NH4 are more preferred, H, Li, Al, and NH4 are even more preferred, and H is particularly preferred. In addition, specific examples of inorganic cations and organic cations are described without symbols and valencies for convenience.
[0111] In general formula (4), R 11 to R 13 Silver independently represents a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. The hydrocarbon group is a monovalent hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably 4 or less. Examples of the hydrocarbon group may include alkyl groups, alkenyl groups, alkynyl groups, etc., with the number of carbon atoms, and methyl or ethyl groups are preferred. R 11 and R 12 Preferably, independently, a hydrogen atom, a methyl group, or an ethyl group, and R13 It is preferable that it be silver, a hydrogen atom, or a methyl group.
[0112] In general formula (4), R 14 ... represents a single bond or a hydrocarbon group having 1 to 8 carbon atoms. The hydrocarbon group is a divalent hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably 4 or less. Examples of the hydrocarbon group may include alkylene groups, alkenylene groups, etc., with the number of carbon atoms mentioned above; among these, at least one selected from the group consisting of methylene groups, ethylene groups, ethylidene groups, propylidene groups, and isopropylidene groups is preferred, and the methylene group is more preferred.
[0113] As the monomer (4), at least one selected from the group consisting of (meth)acrylic acid and its salt, vinylacetic acid (3-butene acid) and its salt, 3-pentene acid and its salt, 4-pentene acid and its salt, 3-hexene acid and its salt, 4-heptene acid and its salt, and 5-hexene acid and its salt is preferred.
[0114] As other monomers, at least one selected from the group consisting of TFE, CTFE, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, HFP, and fluoroalkyl vinyl ether is preferred. (Meth)acrylic acid includes acrylic acid and methacrylic acid.
[0115] The content of other monomer units of the fluorine-containing copolymer is preferably 0.0001 to 50.0 mol% with respect to the total monomer units, more preferably 0.01 mol% or more, even more preferably 0.10 mol% or more, even more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, and particularly preferably 35.0 mol% or less.
[0116] The content of VdF units in the fluorine-containing copolymer is 50.0 to 99.9999 mol% with respect to the total monomer units, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, more preferably 99.99 mol% or less, and even more preferably 99.90 mol% or less.
[0117] When a fluorine-containing copolymer contains a fluorinated monomer unit as another monomer unit, the content of the fluorinated monomer unit is preferably 0.0001 to 50.0 mol% with respect to the total monomer unit, more preferably 2.0 mol% or more, even more preferably 3.0 mol% or more, particularly preferably 4.0 mol% or more, more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, and particularly preferably 35.0 mol% or less.
[0118] When a fluorine-containing copolymer contains a fluorinated monomer unit as another monomer unit, the content of the VdF unit of the fluorine-containing copolymer is 50.0 to 99.999 mol% with respect to the total monomer units, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, more preferably 98.0 mol% or less, even more preferably 97.0 mol% or less, and particularly preferably 96.0 mol% or less.
[0119] When the fluorine-containing copolymer contains non-fluorinated monomer units, such as polar group-containing monomers, as other monomer units, the content of the non-fluorinated monomer units is preferably 0.0001 to 50.0 mol% with respect to the total monomer units, more preferably 0.01 mol% or more, even more preferably 0.10 mol% or more, even more preferably 5.0 mol% or less, even more preferably 3.0 mol% or less, and particularly preferably 1.5 mol% or less.
[0120] When a fluorine-containing copolymer contains non-fluorinated monomer units as other monomer units, the content of VdF units of the fluorine-containing copolymer is preferably 50.0 to 99.999 mol% with respect to the total monomer units, more preferably 95.0 mol% or more, even more preferably 97.0 mol% or more, particularly preferably 98.5 mol% or more, more preferably 99.99 mol% or less, and even more preferably 99.90 mol% or less.
[0121] In the present disclosure, the composition of the fluorine-containing copolymer is, for example, 19 It can be measured by F-NMR measurement. In addition, if the fluorine-containing copolymer contains a polar group-containing monomer unit as another monomer unit, the content of the polar group-containing monomer unit can be measured by acid-base titration of the acid group, for example, when the polar group is an acid group such as a carboxylic acid.
[0122] The weight average molecular weight (in polystyrene equivalent) of the fluorine-containing copolymer is preferably 10,000 to 3,000,000, more preferably 30,000 or more, even more preferably 50,000 or more, particularly preferably 200,000 or more, more preferably 240,000 or less, even more preferably 220,000 or less, and particularly preferably 200,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0123] The number average molecular weight (in polystyrene equivalent) of the fluorine-containing copolymer is preferably 7,000 to 1,500,000, more preferably 21,000 or more, even more preferably 35,000 or more, even more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0124] As fluorine-containing copolymers, for example, VdF / (meth)acrylic acid copolymer, VdF / TFE copolymer, VdF / HFP copolymer, VdF / fluoroalkylvinyl ether copolymer, VdF / TFE / HFP copolymer, VdF / 2,3,3,3-tetrafluoropropene copolymer, VdF / TFE / 2,3,3,3-tetrafluoropropene copolymer, VdF / TFE / (meth)acrylic acid copolymer, VdF / HFP / (meth)acrylic acid copolymer, VdF / CTFE copolymer, VdF / TFE / 4-pentene acid copolymer, VdF / TFE / 3-butene acid copolymer, VdF / TFE / HFP / (meth)acrylic acid copolymer, VdF / TFE / HFP / 4-pentene acid copolymer, Examples include VdF / TFE / HFP / 3-butene acid copolymer, VdF / TFE / 2-carboxyethyl acrylate copolymer, VdF / TFE / HFP / 2-carboxyethyl acrylate copolymer, VdF / TFE / acryloyloxyethyl succinic acid copolymer, VdF / TFE / HFP / acryloyloxyethyl succinic acid copolymer, etc.
[0125] As for the fluorine-containing copolymer, at least one selected from the group consisting of VdF / TFE copolymer, VdF / CTFE copolymer, VdF / (meth)acrylic acid copolymer, VdF / 2,3,3,3-tetrafluoropropene copolymer, VdF / HFP copolymer, and VdF / fluoroalkyl vinyl ether copolymer is preferred.
[0126] The VdF / TFE copolymer contains VdF units and TFE units. By using the VdF / TFE copolymer as the copolymer, the composition can be formed very easily, and a composition with excellent slurry stability can be obtained, allowing for the formation of a coating layer with excellent flexibility. The content of VdF units is preferably 50.0 to 95.0 mol% with respect to the total monomer units of the VdF / TFE copolymer, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, even more preferably 92.0 mol% or less, and even more preferably 89.0 mol% or less. The content of TFE units is preferably 50.0 to 5.0 mol% with respect to the total monomer units of the VdF / TFE copolymer, more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, even more preferably 8.0 mol% or more, and even more preferably 11.0 mol% or more.
[0127] The VdF / TFE copolymer may include, in addition to VdF units and TFE units, units based on monomers copolymerizable with VdF and TFE (excluding VdF and TFE). The content of units based on monomers copolymerizable with VdF and TFE is preferably 3.0 mol% or less with respect to the total monomer units of the VdF / TFE copolymer in terms of electrolyte swelling resistance.
[0128] Examples of monomers copolymerizable with VdF and TFE include the aforementioned fluorinated monomers and the aforementioned non-fluorinated monomers. Among the monomers copolymerizable with VdF and TFE, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, and at least one selected from the group consisting of HFP, 2,3,3,3-tetrafluoropropene, and monomer (4) is more preferred.
[0129] The weight average molecular weight (in polystyrene equivalent) of the VdF / TFE copolymer is preferably 50,000 to 200,000, more preferably 80,000 to 170,000, and even more preferably 100,000 to 150,000.
[0130] The number average molecular weight (in polystyrene equivalent) of the VdF / TFE copolymer is 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0131] The VdF / CTFE copolymer contains VdF units and CTFE units. By using the VdF / CTFE copolymer as the copolymer, the composition can be formed very easily, and a coating layer that adheres very firmly to the metal foil can be formed. The content of VdF units is preferably 80.0 to 98.0 mol% with respect to the total monomer units of the VdF / CTFE copolymer, more preferably 85.0 mol% or more, even more preferably 90.0 mol% or more, even more preferably 97.5 mol% or less, and even more preferably 97.0 mol% or less. The content of CTFE units is preferably 20.0 to 2.0 mol% with respect to the total monomer units of the VdF / CTFE copolymer, more preferably 15.0 mol% or less, even more preferably 10.0 mol% or less, even more preferably 2.5 mol% or more, and even more preferably 3.0 mol% or more.
[0132] The VdF / CTFE copolymer may include, in addition to VdF units and CTFE units, units based on monomers capable of copolymerizing with VdF and CTFE (excluding VdF and CTFE). The content of units based on monomers capable of copolymerizing with VdF and CTFE is preferably 3.0 mol% or less with respect to the total monomer units of the VdF / CTFE copolymer, in terms of electrolyte swelling properties.
[0133] As monomers copolymerizable with VdF and CTFE, the above-mentioned fluorinated monomer and the above-mentioned non-fluorinated monomer may be cited. Among the monomers copolymerizable with VdF and CTFE, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, at least one selected from the group consisting of TFE, HFP, 2,3,3,3-tetrafluoropropene and monomer (4) is more preferred, and TFE is even more preferred.
[0134] The weight average molecular weight (in polystyrene equivalent) of the VdF / CTFE copolymer is preferably 50,000 to 200,000, more preferably 80,000 to 170,000, and even more preferably 100,000 to 150,000.
[0135] The number average molecular weight (in polystyrene equivalent) of the VdF / CTFE copolymer is preferably 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0136] The VdF / (meth)acrylic acid copolymer contains VdF units and (meth)acrylic acid units. By using the VdF / (meth)acrylic acid copolymer as the copolymer, the composition can be formed very easily, and a coating layer that adheres very firmly to the metal foil can be formed. The content of (meth)acrylic acid units is preferably 0.0001 to 5.0 mol% with respect to the total monomer units, more preferably 0.01 to 3.0 mol%, and even more preferably 0.10 to 1.5 mol%.
[0137] The content of VdF units in the VdF / (meth)acrylic acid copolymer is preferably 95.0 to 99.9999 mol% with respect to the total monomer units, more preferably 97.0 to 99.99 mol%, and even more preferably 98.5 to 99.90 mol%.
[0138] The weight average molecular weight (in polystyrene equivalent) of the VdF / (meth)acrylic acid copolymer is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, particularly preferably 200,000 or more, more preferably 240,000 or less, even more preferably 220,000 or less, and particularly preferably 200,000 or less.
[0139] The number average molecular weight (in polystyrene equivalent) of the VdF / (meth)acrylic acid copolymer is preferably 20,000 to 1,500,000, more preferably 40,000 or more, even more preferably 70,000 or more, particularly preferably 140,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less.
[0140] The VdF / 2,3,3,3-tetrafluoropropene copolymer contains VdF units and 2,3,3,3-tetrafluoropropene units. By using the VdF / 2,3,3,3-tetrafluoropropene copolymer as the copolymer, a composition can be formed very easily, and a coating layer with excellent flexibility and conductivity can be formed. The content of VdF units is preferably 50.0 to 98.0 mol% with respect to the total monomer units of the VdF / 2,3,3,3-tetrafluoropropene copolymer, more preferably 55.0 mol% or more, even more preferably 60.0 mol% or more, particularly preferably 65.0 mol% or more, more preferably 97.0 mol% or less, and even more preferably 96.0 mol% or less. The content of 2,3,3,3-tetrafluoropropene units is preferably 2.0 to 50.0 mol% with respect to the total monomer units of the VdF / TFE copolymer, more preferably 3.0 mol% or more, even more preferably 4.0 mol% or more, even more preferably 45.0 mol% or less, even more preferably 40.0 mol% or less, and particularly preferably 35.0 mol% or less.
[0141] The VdF / 2,3,3,3-tetrafluoropropene copolymer may comprise, in addition to the VdF unit and the 2,3,3,3-tetrafluoropropene unit, a unit based on a monomer capable of copolymerizing with VdF and 2,3,3,3-tetrafluoropropene (excluding VdF and 2,3,3,3-tetrafluoropropene). The content of the unit based on the monomer capable of copolymerizing with VdF and 2,3,3,3-tetrafluoropropene is preferably 3.0 mol% or less with respect to the total monomer units of the VdF / 2,3,3,3-tetrafluoropropene copolymer, in terms of electrolyte swelling properties.
[0142] As monomers capable of copolymerizing with VdF and 2,3,3,3-tetrafluoropropene, examples include the aforementioned fluorinated monomer and the aforementioned non-fluorinated monomer. Among the monomers capable of copolymerizing with VdF and 2,3,3,3-tetrafluoropropene, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, and at least one selected from the group consisting of TFE, HFP, and monomer (4) is more preferred.
[0143] The weight average molecular weight (in polystyrene equivalent) of the VdF / 2,3,3,3-tetrafluoropropene copolymer is preferably 10,000 to 20,000,000, more preferably 30,000 to 17,000,000, and even more preferably 5,000 to 15,000,000.
[0144] The number average molecular weight (in polystyrene equivalent) of the VdF / 2,3,3,3-tetrafluoropropene copolymer is preferably 7,000 to 1,400,000, more preferably 21,000 to 1,300,000, and even more preferably 35,000 to 1,200,000.
[0145] The VdF / HFP copolymer contains VdF units and HFP units. By using the VdF / HFP copolymer as the copolymer, the composition can be formed very easily, and a coating layer that adheres very firmly to the metal foil can be formed. The content of VdF units is preferably 80.0 to 98.0 mol% with respect to the total monomer units of the VdF / HFP copolymer, more preferably 83.0 mol% or more, even more preferably 85.0 mol% or more, even more preferably 97.0 mol% or less, and even more preferably 96.0 mol% or less. The content of HFP units is preferably 20.0 to 2.0 mol% with respect to the total monomer units of the VdF / HFP copolymer, more preferably 17.0 mol% or less, even more preferably 15.0 mol% or less, even more preferably 3.0 mol% or more, and even more preferably 4.0 mol% or more.
[0146] The VdF / HFP copolymer may include, in addition to VdF units and HFP units, units based on monomers copolymerizable with VdF and HFP (excluding VdF and HFP). The content of units based on monomers copolymerizable with VdF and HFP is preferably 3.0 mol% or less with respect to the total monomer units of the VdF / HFP copolymer in terms of electrolyte swelling properties.
[0147] As monomers copolymerizable with VdF and HFP, the above-mentioned fluorinated monomer and the above-mentioned non-fluorinated monomer may be cited. Among the monomers copolymerizable with VdF and HFP, at least one selected from the group consisting of fluorinated monomers and polar group-containing monomers is preferred, at least one selected from the group consisting of TFE, 2,3,3,3-tetrafluoropropene and monomer (4) is more preferred, and monomer (4) is even more preferred.
[0148] The weight average molecular weight (in polystyrene equivalent) of the VdF / HFP copolymer is preferably 50,000 to 200,000, more preferably 80,000 to 170,000, and even more preferably 100,000 to 150,000.
[0149] The number average molecular weight (in polystyrene equivalent) of the VdF / HFP copolymer is preferably 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0150] The VdF / fluoroalkyl vinyl ether copolymer contains VdF units and fluoroalkyl vinyl ether units. The content of VdF units is preferably 80.0 to 98.0 mol% with respect to the total monomer units of the VdF / fluoroalkyl vinyl ether copolymer, more preferably 83.0 mol% or more, even more preferably 85.0 mol% or more, even more preferably 97.0 mol% or less, and even more preferably 96.0 mol% or less. The content of fluoroalkyl vinyl ether units is preferably 20.0 to 2.0 mol% with respect to the total monomer units of the VdF / fluoroalkyl vinyl ether copolymer, more preferably 17.0 mol% or less, even more preferably 15.0 mol% or less, even more preferably 3.0 mol% or more, and even more preferably 4.0 mol% or more.
[0151] The VdF / fluoroalkylvinyl ether copolymer may comprise, in addition to the VdF unit and the fluoroalkylvinyl ether unit, a unit based on a monomer copolymerizable with VdF and fluoroalkylvinyl ether (excluding VdF and fluoroalkylvinyl ether). The content of the unit based on the monomer copolymerizable with VdF and fluoroalkylvinyl ether is preferably 3.0 mol% or less with respect to the total monomer units of the VdF / fluoroalkylvinyl ether copolymer, in terms of electrolyte swelling resistance.
[0152] As monomers copolymerizable with VdF and fluoroalkyl vinyl ether, the above-described fluorinated monomer and the above-described non-fluorinated monomer may be cited. Among the monomers copolymerizable with VdF and fluoroalkyl vinyl ether, at least one selected from the group consisting of fluorinated monomers and monomers containing polar groups is preferred, at least one selected from the group consisting of TFE, 2,3,3,3-tetrafluoropropene and monomer (4) is more preferred, and monomer (4) is even more preferred.
[0153] The weight average molecular weight (in polystyrene equivalent) of the VdF / fluoroalkyl vinyl ether copolymer is preferably 50,000 to 200,000, more preferably 80,000 to 170,000, and even more preferably 100,000 to 150,000.
[0154] The number average molecular weight (in polystyrene equivalent) of the VdF / fluoroalkyl vinyl ether copolymer is preferably 35,000 to 1,400,000, more preferably 40,000 to 1,300,000, and even more preferably 50,000 to 1,200,000.
[0155] It is also preferable that the binder contains PVdF. PVdF is a polymer containing VdF units and is a polymer different from the fluorine-containing copolymer described above. PVdF may be a VdF homopolymer containing only VdF units, or a polymer containing VdF units and units based on monomers copolymerizable with VdF.
[0156] In the above PVdF, as a monomer copolymerizable with VdF, it is preferable that the monomer be different from tetrafluoroethylene (TFE). That is, it is preferable that PVdF not contain TFE units.
[0157] In the above PVdF, monomers copolymerizable with VdF may include fluorinated monomers, non-fluorinated monomers, etc., and fluorinated monomers are preferred. Examples of the above fluorinated monomers include vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, etc. Examples of the above non-fluorinated monomers include ethylene, propylene, etc.
[0158] In the above PVdF, as a monomer copolymerizable with VdF, at least one fluorinated monomer selected from the group consisting of CTFE, fluoroalkyl vinyl ether, HFP, and 2,3,3,3-tetrafluoropropene is preferred, and at least one fluorinated monomer selected from the group consisting of CTFE, HFP, and fluoroalkyl vinyl ether is more preferred.
[0159] In the above PVdF, the content of monomer units copolymerizable with VdF is preferably 0 to 5.0 mol% with respect to the total monomer units, and more preferably 0 to 3.0 mol%. In the above PVdF, the content of fluorinated monomer units copolymerizable with VdF is preferably less than 5.0 mol% with respect to the total monomer units, more preferably less than 3.0 mol%, and even more preferably less than 1.0 mol%.
[0160] In the present disclosure, the composition of PVdF is, for example, 19 It can be measured by F-NMR measurement.
[0161] The above PVdF may have a polar group. The above polar group is not particularly limited as long as it is a polar functional group, but at least one selected from the group consisting of a carbonyl group containing a carbonyl group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfate group, a phosphate group, an amino group, an amide group, and an alkoxy group is preferred, at least one selected from the group consisting of a carbonyl group containing a carbonyl group, an epoxy group, and a hydroxyl group is more preferred, and a carbonyl group containing a carbonyl group is even more preferred. The above hydroxyl group does not include a hydroxyl group that constitutes a part of the above carbonyl group containing a carbonyl group. In addition, the above amino group is a monovalent functional group obtained by removing hydrogen from ammonia, a primary or secondary amine.
[0162] The above carbonyl group containing group is a functional group having a carbonyl group (-C(=O)-). As the above carbonyl group containing group, a group represented by the general formula -COOR (where R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group) or a carboxylic acid anhydride group is preferred, and a group represented by the general formula -COOR is more preferred. The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3. Specific examples of groups represented by the general formula -COOR include -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, -COOC2H5, etc. General formula: The group represented by -COOR is -COOH, or if it contains -COOH, -COOH may be a carboxylate such as a metal carboxylate salt or an ammonium carboxylate salt.
[0163] In addition, the carbonyl group containing the above may be a contribution represented by the general formula: -X-COOR (where X is composed of 2 to 15 atoms in the main chain, and the molecular weight of the atomic group represented by X is preferably 350 or less. R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group). The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3.
[0164] As the above amide group, a group represented by the general formula: -CO-NRR' (R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group) or a bond represented by the general formula: -CO-NR"- (R" represents a hydrogen atom, a substituted or unsubstituted alkyl group or a substituted or unsubstituted phenyl group) is preferred.
[0165] The above polar group may be introduced into PVdF by polymerizing VdF with a monomer having the above polar group (hereinafter referred to as a polar group-containing monomer) or by reacting PVdF with a compound having the above polar group; however, from the perspective of productivity, it is preferable to polymerize VdF with the polar group-containing monomer.
[0166] When VdF is polymerized with the above-mentioned polar group-containing monomer, PVdF containing VdF units and polar group-containing monomer units is obtained. That is, it is preferable that PVdF contains the above-mentioned polar group-containing monomer units. The content of the above-mentioned polar group-containing monomer units is preferably 0.001 to 5.0 mol% with respect to the total monomer units, more preferably 0.01 to 3.0 mol%, and even more preferably 0.10 to 1.5 mol%.
[0167] In the present disclosure, the content of the polar group-containing monomer unit in PVdF can be measured by acid-base titration of the acid group, for example, when the polar group is an acid group such as a carboxylic acid.
[0168] The above polar group-containing monomers include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated monobasic acids such as (meth)acrylic acid, crotonic acid, vinylacetic acid (3-butene acid), 3-pentene acid, 4-pentene acid, 3-hexene acid, and 4-heptene acid; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidenemalonic acid esters such as dimethyl methylidenemalonicate; vinylcarboxyalkyl ethers such as vinylcarboxymethyl ether and vinylcarboxyethyl ether; and carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate. Examples include (meth)acryloyloxyalkyl dicarboxylic acid esters such as acryloyloxyethyl succinic acid, methacryloyloxyethyl succinic acid, acryloyloxyethylphthalic acid, acryloyloxypropyl succinic acid, and methacryloyloxyethylphthalic acid; monoesters of unsaturated dibasic acids such as maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, and citraconic acid monoethyl ester; etc.
[0169] When introducing the polar group into PVdF by reacting PVdF with a compound having the polar group, the compound having the polar group may be a monomer containing the polar group, or a silane-based coupling agent or a titanate-based coupling agent having a group reactive to PVdF and a hydrolyzable group. The hydrolyzable group is preferably an alkoxy group. When a coupling agent is used, the polar group can be added to PVdF by reacting it with PVdF dissolved or swollen in a solvent.
[0170] As for PVdF, a PVdF obtained by partially dehydrofluoricing PVdF with a base and then further reacting the partially dehydrofluoriced PVdF with an oxidizing agent may also be used. Examples of the oxidizing agent include hydrogen peroxide, hypochlorite, palladium halide, chromium halide, alkali metal permanganate, peroxide compounds, alkyl peroxide, alkyl persulfate, etc.
[0171] The content of VdF units in PVdF is preferably greater than 95.0 mol% with respect to the total monomer units, more preferably greater than 97.0 mol%, and even more preferably greater than 99.0 mol%.
[0172] In addition, the content of VdF units of PVdF is preferably 95.0 to 99.999 mol% with respect to the total monomer units, more preferably 97.0 mol% or more, even more preferably 98.5 mol% or more, even more preferably 99.99 mol% or less, and even more preferably 99.90 mol% or less.
[0173] The weight-average molecular weight of PVdF (converted to polystyrene) is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, particularly preferably 200,000 or more, more preferably 240,000 or less, even more preferably 220,000 or less, and particularly preferably 200,000 or less. The weight-average molecular weight can be measured by gel permeation chromatography (GPC) using N,N-dimethylformamide as a solvent. Additionally, the weight-average molecular weight of PVdF may be 1,000,000 or more, or 1,500,000 or more.
[0174] The number average molecular weight of PVdF (converted to polystyrene) is preferably 20,000 to 1,500,000, more preferably 40,000 or more, even more preferably 70,000 or more, particularly preferably 140,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0175] The melting point of PVdF is preferably 100 to 240°C. The melting point can be determined as the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimetry (DSC) device.
[0176] The binder is a fluorine-containing polymer, and it is also preferable to contain a fluorine-containing copolymer containing PVdF and VdF units and monomer units other than VdF.
[0177] When the binder contains PVdF and a fluorine-containing copolymer, the mass ratio of PVdF to the fluorine-containing copolymer in the binder (PVdF / fluorine-containing copolymer) is preferably 99 / 1 to 1 / 99, more preferably 97 / 3 to 3 / 97, even more preferably 95 / 5 to 5 / 95, particularly preferably 90 / 10 to 10 / 90, particularly preferably 85 / 15 to 15 / 85, and most preferably 80 / 20 to 40 / 60.
[0178] The binder may include other polymers in addition to PVdF and fluorine-containing copolymers. Examples of other polymers include polymethacrylate, polymethyl methacrylate, polyacrylonitrile, polyimide, polyamide, polyamideimide, polycarbonate, styrene rubber, butadiene rubber, etc.
[0179] The content of the fluorine-containing copolymer in the binder is preferably 1 mass% or more, more preferably 3 mass% or more, even more preferably 5 mass% or more, particularly preferably 10 mass% or more, most preferably 15 mass% or more, and may be 100 mass% or less, with respect to the mass of the binder.
[0180] The content of the binder in the composition of the present disclosure is preferably 0.1 to 20 mass% with respect to the mass of the composition, more preferably 0.2 to 10 mass%, and even more preferably 0.5 to 3 mass%.
[0181] The viscosity of the composition of the present disclosure is preferably 5 to 8000 mPa·s, more preferably 100 to 5000 mPa·s, and even more preferably 100 to 2000 mPa·s. The viscosity can be measured using a Type B viscometer (Brookfield, LV-DV2T) under conditions of 25°C, rotor No. SC4-21, and rotation speed of 20 rpm.
[0182] (use)
[0183] The composition of the present disclosure can be suitably used to form an electrode of an electrochemical device. The composition of the present disclosure may be an electrode-forming composition.
[0184] The composition of the present disclosure can be suitably used as a material for forming electrodes of batteries such as secondary batteries and capacitors. The battery may be a primary battery, a storage battery (secondary battery), or a storage element. The battery may be a non-aqueous electrolyte battery. Non-aqueous electrolyte batteries include all batteries equipped with an electrolyte and a power generation element. Examples of non-aqueous electrolyte batteries include lithium-ion primary batteries, lithium-ion secondary batteries, nickel-hydrogen batteries, lithium-ion capacitors, electric double-layer capacitors, sodium-ion secondary batteries, etc.
[0185] The composition of the present disclosure may be a composition for forming a positive electrode used in the production of a positive electrode, or a composition for forming a negative electrode used in the production of a negative electrode. The electrode material layer formed by the composition of the present disclosure may be a positive electrode material layer or a negative electrode material layer.
[0186] (Other ingredients)
[0187] The composition of the present disclosure preferably further contains a powder electrode material (except for the single-layer carbon nanotube).
[0188] The powder electrode material is a powder electrode material used in a battery, and it is preferable that it includes an electrode active material. The electrode active material is divided into a positive electrode active material and a negative electrode active material.
[0189] As a positive electrode active material, a material capable of electrochemically absorbing and releasing lithium ions may be used, and a lithium composite oxide is preferred, and a lithium transition metal composite oxide is more preferred. As a positive electrode active material, a lithium-containing transition metal phosphate compound is also preferred. It is also preferred that the positive electrode active material be a material containing lithium and at least one transition metal, such as a lithium transition metal composite oxide or a lithium-containing transition metal phosphate compound.
[0190] As the transition metal of the lithium transition metal composite oxide, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. Specific examples of lithium transition metal composite oxides include lithium-cobalt composite oxides such as LiCoO2, lithium-nickel composite oxides such as LiNiO2, lithium-manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3, etc., and those in which some of the transition metal atoms forming the main component of these lithium transition metal composite oxides are substituted with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc. Examples of the above-mentioned substitutes include lithium-nickel-manganese composite oxides, lithium-nickel-cobalt-aluminum composite oxides, lithium-nickel-cobalt-manganese composite oxides, lithium-manganese-aluminum composite oxides, lithium-titanium composite oxides, etc. More specifically, LiNiO . 5Mn0 . 5O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi0 .33 Co0 . 33 Mn0 . 33 O2, LiNi0 . 5Mn0 . 3Co0 . 2O2, LiNi0 . 6Mn0 . 2Co0 . 2O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiMn1 . 8Al0 . 2O4, LiMn1 . 5Ni0 . 5O4, Li4Ti5O 12 , LiNi0 . 82 Co0 . 15 Al0 . 03 O2 You can lift the back.
[0191] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred, and specific examples of the lithium-containing transition metal phosphate compound include, for instance, LiFePO4, Li3Fe2(PO4)3, and LiFeP2O7 Iron phosphates such as LiCoPO4 Examples include cobalt phosphates, and those in which some of the transition metal atoms that form the main component of these lithium transition metal phosphate compounds are replaced with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, and Si.
[0192] In particular, in terms of high voltage, high energy density, or charge / discharge cycle characteristics, LiCoO2, LiNiO2, LiMn2O4, LiNiO . 82 Co0 . 15 Al0 . 03 O2, LiNi0 .33 Mn0 . 33 Co0 . 33 O2, LiNi0 . 5Mn0 . 3Co0 . 2O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2 and LiFePO4 are preferred.
[0193] In addition, as a lithium transition metal composite oxide, a lithium-nickel composite oxide is preferred, and general formula (7):
[0194] General formula (7): Li y Ni1 - x M x O2
[0195] (In the equation, x is 0.01≤x≤0.5, y is 0.9≤y≤1.2, and M represents a metal atom (excluding Li and Ni).)
[0196] A lithium-nickel composite oxide represented by is more preferable. A lithium transition metal composite oxide with a high nickel content like this is beneficial for increasing the capacity of secondary batteries.
[0197] In general formula (7), x is a coefficient satisfying 0.01≤x≤0.5, and is preferably 0.05≤x≤0.4 and more preferably 0.10≤x≤0.3 in order to obtain a secondary battery with a higher capacity.
[0198] In general formula (7), the metal atoms of M may include V, Ti, Cr, Mn, Fe, Co, Cu, Al, Zn, Mg, Ga, Zr, Si, etc. As for the metal atoms of M, transition metals such as V, Ti, Cr, Mn, Fe, Co, Cu, etc., or a combination of the above transition metals and other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Mg, Ga, Zr, Si, etc. are preferred.
[0199] As a lithium transition metal composite oxide with a high nickel content, LiNiO . 80 Co0 . 15 Al0 . 05 O2, LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi0 . 33 Mn0 . 33 Co0 . 33 O2, LiNi0 . 5Mn0 . 3Co0 . 2O2, LiNi0 . 6Mn0 . 2Co0 . 2O2, LiNi 0.8 Mn 0.1 Co 0.1 O2 and LiNi0 . 90 Mn0 . 05 Co0 . 05 At least one type selected from the group consisting of O2 is preferred, and LiNiO . 82 Co0 . 15 Al0 . 03 O2, LiNi0 . 6Mn0 . 2Co0 . 2O2, and LiNiO . 8Mn0 . 1Co0. At least one type selected from the group consisting of 1O2 is more preferable.
[0200] In addition, a material with a composition different from that of the main positive electrode active material may be attached to the surface of these positive electrode active materials. Examples of surface-attached materials include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.
[0201] These surface attachment materials can be attached to the surface of a positive electrode active material by, for example, by a method of dissolving or suspending in a solvent and adding to the positive electrode active material and drying, a method of dissolving or suspending a surface attachment material precursor in a solvent and adding to the positive electrode active material and reacting by heating, etc., or by adding to the positive electrode active material precursor and simultaneously calcining.
[0202] As for the amount of surface-attached material, in terms of mass relative to the positive electrode active material, the lower limit is preferably 0.1 ppm or more, more preferably 1 ppm or more, even more preferably 10 ppm or more, and the upper limit is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. The surface-attached material can suppress the oxidation reaction of the non-aqueous electrolyte on the surface of the positive electrode active material, thereby improving battery life, but if the amount of attachment is too small, the effect is not sufficiently manifested, and if it is too large, resistance may increase because it hinders the entry and exit of lithium ions.
[0203] The particle shapes of the positive electrode active material include conventionally used bulk, polyhedral, spherical, elliptical, plate-like, needle-like, and columnar shapes; however, among these, it is preferable that primary particles aggregate to form secondary particles, and that the shape of the secondary particles is spherical or elliptical. Typically, as the active material in the electrode of an electrochemical device expands and contracts during charging and discharging, degradation such as the destruction of the active material or the breakage of conductive paths due to stress is likely to occur. Therefore, rather than a single-particle active material consisting only of primary particles, it is preferable to have primary particles aggregated to form secondary particles, as this alleviates the stress of expansion and contraction and prevents degradation. Furthermore, spherical or elliptical particles are preferable to plate-like equiaxially oriented particles because they have less orientation during electrode molding, resulting in less expansion and contraction of the electrode during charging and discharging, and also facilitate uniform mixing with the conductive agent when manufacturing the electrode.
[0204] The tap density of the positive electrode active material is typically 1.3 g / cm³ or higher, preferably 1.5 g / cm³ or higher, more preferably 1.6 g / cm³ or higher, and most preferably 1.7 g / cm³ or higher. If the tap density of the positive electrode active material falls below the above lower limit, the amount of dispersion medium required during the formation of the positive electrode material layer increases, along with the required amount of conductive agent or copolymer, and the filling rate of the positive electrode active material in the positive electrode material layer is restricted, which may result in a limitation of battery capacity. By using a metal composite oxide powder with a high tap density, a high-density positive electrode material layer can be formed. Generally, a higher tap density is preferable and there is no specific upper limit; however, if it is too high, the diffusion of lithium ions using a non-aqueous electrolyte within the positive electrode material layer becomes rate-limited, and load characteristics may easily deteriorate; therefore, it is typically 2.5 g / cm³ or lower, preferably 2.4 g / cm³ or lower.
[0205] The tap density of the positive electrode active material is defined as the density obtained from the volume and weight of the sample at that time by passing the sample through a sieve with a mesh size of 300 μm, dropping it into a tapping cell of 20 cm³ to fill the cell volume, and then performing 1,000 tappings with a stroke length of 10 mm using a powder density meter (e.g., a tap denser made by Seishin Kikyo Co., Ltd.).
[0206] The median diameter d50 of the particles of the positive electrode active material (the diameter of the secondary particles in cases where primary particles aggregate to form secondary particles) is typically 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, most preferably 3 μm or more, typically 20 μm or less, preferably 18 μm or less, more preferably 16 μm or less, and most preferably 15 μm or less. If it falls below the lower limit, a high bulk density product may not be obtained, and if it exceeds the upper limit, lithium diffusion within the particles takes time, which may lead to a decrease in battery performance or cause problems such as streaking when manufacturing the positive electrode of the battery—that is, when slurrying the active material with a conductive agent or copolymer with a solvent and applying it in the form of a thin film. Here, by mixing two or more types of positive electrode active materials having different median diameters d50, the chargeability during the manufacturing of the positive electrode may be further improved.
[0207] In addition, the median diameter d50 in the present disclosure is measured by a known laser diffraction / scattering particle size distribution measuring device. When using the LA-920 manufactured by HORIBA as the particle size distribution meter, a 0.1 mass% aqueous sodium hexametaphosphate solution is used as the dispersion medium used during measurement, and the measurement is performed by setting the refractive index to 1.24 after 5 minutes of ultrasonic dispersion.
[0208] In cases where primary particles aggregate to form secondary particles, the average primary particle size of the positive electrode active material is typically 0.01 μm or more, preferably 0.05 μm or more, more preferably 0.08 μm or more, and most preferably 0.1 μm or more; and typically 3 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and most preferably 0.6 μm or less. If the upper limit is exceeded, it becomes difficult to form spherical secondary particles, which adversely affects powder packing efficiency or significantly reduces the specific surface area, thereby increasing the likelihood of degraded battery performance, such as output characteristics. Conversely, if the lower limit is lowered, problems such as reduced reversibility of charge and discharge may occur because the crystals are typically underdeveloped. In addition, the primary particle size is measured by observation using a scanning electron microscope (SEM). Specifically, the longest value of the intercept by the left and right boundary lines of the primary particles with respect to a horizontal straight line is obtained for any 50 primary particles using a photograph at a magnification of 10,000 times, and the average value is taken.
[0209] The BET specific surface area of the positive electrode active material is 0.2 m² / g or more, preferably 0.3 m² / g or more, more preferably 0.4 m² / g or more, and 4.0 m² / g or less, preferably 2.5 m² / g or less, more preferably 1.5 m² / g or less. If the BET specific surface area is smaller than this range, battery performance is likely to degrade, and if it is larger, it becomes difficult to increase the tap density, which may cause problems with coating properties when forming the positive electrode material layer.
[0210] The BET specific surface area is defined as a value measured by the nitrogen adsorption BET 1-point method by the gas flow method, using a surface area meter (e.g., an Okura Riken fully automatic surface area measuring device), pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas that is accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.
[0211] As a method for manufacturing positive electrode active materials, general methods for manufacturing inorganic compounds are used. In particular, various methods are considered for producing spherical or elliptical active materials; for example, transition metal raw materials such as transition metal nitrates and sulfates, along with raw materials of other elements as needed, are dissolved or ground and dispersed in a solvent such as water, and a spherical precursor is produced and recovered by adjusting the pH while stirring. This is then dried as needed, followed by LiOH, Li2CO3, LiNO3 A method for obtaining an active material by adding a Li source such as and calcining at a high temperature, wherein a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide, or oxide, and, if necessary, a raw material of another element, are dissolved or ground and dispersed in a solvent such as water, and the mixture is dried and molded using a spray dryer or the like to form a spherical or elliptical precursor, and to this, LiOH, Li2CO3, LiNO3 A method for obtaining an active material by adding a Li source such as Li-22 and calcining at high temperature, and also transition metal raw materials such as transition metal nitrates, sulfates, hydroxides, and oxides, and LiOH, Li2CO3, LiNO3 Examples of methods include dissolving or grinding and dispersing a Li source and, if necessary, a raw material of another element in a solvent such as water, drying and molding it with a spray dryer or the like to form a spherical or elliptical precursor, and then calcining this at a high temperature to obtain an active material.
[0212] In addition, in the present disclosure, the positive electrode active material may be used as a single type, or two or more types with different compositions or different powder properties may be used in any combination and ratio.
[0213] When the composition of the present disclosure contains a positive electrode active material, the content of single-layer carbon nanotubes is preferably 0.001 to 10 parts by mass per 100 parts by mass of the positive electrode active material.
[0214] When the composition of the present disclosure contains a positive electrode active material, the content of the binder is preferably 0.01 to 5.0 parts by mass per 100 parts by mass of the positive electrode active material.
[0215] As a negative electrode active material, a negative electrode active material that exhibits a potential of 2.5V or less based on Li when alloyed with Li or combined with Li can be cited.
[0216] As a negative electrode active material, a negative electrode active material containing metal may be used. The metal included in the negative electrode active material is typically a metal capable of electrochemically alloying with alkali metals such as Li and Na.
[0217] Examples of negative electrode active materials include: metal elements capable of electrochemically alloying with Li, such as Si, Zn, Sn, W, Al, Sb, Ge, Bi, and In; alloys containing Si, Zn, Sn, W, Al, Sb, Ge, Bi, and In; lithium alloys such as lithium aluminum alloys and lithium tin alloys; metal oxides such as tin oxide or silicon oxide; and lithium titanium dioxide. Among these, one or more types may be used as negative electrode active materials.
[0218] As a negative electrode active material, a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb, and Ti is preferred, and Si (elementary Si), oxide of Si, alloy containing Si, Sn (Sn carrier), oxide of Sn, and alloy containing Sn are more preferred, and Si and SiO x (0 <x<2)로 이루어지는 군에서 선택되는 적어도 1종이 더욱 바람직하다.
[0219] In addition, carbonaceous materials such as graphite powder may be used as the negative electrode active material. Carbonaceous materials can be used together with a negative electrode active material containing metal. As carbonaceous materials, natural graphite, artificial carbonaceous materials, artificial graphitic materials, carbonaceous materials {e.g., natural graphite, coal-based coke, petroleum-based coke, coal-based pitch, petroleum-based pitch, or pitches oxidized, needle coke, pitch coke, and carbon materials partially graphitized therefrom, thermal decomposition products of organic materials such as furnace black, acetylene black, Ketjen black, and pitch-based carbon fibers, carbonizable organic materials (e.g., coal tar pitch ranging from soft to hard pitch, or coal-based heavy oils such as dry distillation liquefied oil, straight-line heavy oils such as atmospheric residue and vacuum residue, cracking-type petroleum heavy oils such as ethylene tar produced as a byproduct during the thermal decomposition of crude oil, naphtha, etc., also aromatic hydrocarbons such as acenaphtylene, decarycyclene, anthracene, phenanthrene, etc., N-ring compounds such as phenazine or acridine, S-ring compounds such as thiophene and bithiophene, biphenyl, terphenyl, etc. Examples include carbonaceous materials that have been heat-treated at least once in a range of 400 to 3200°C, wherein the carbonaceous material comprises: polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, insoluble products among these, organic polymers such as nitrogen-containing polyacrylonitrile and polypyrrole, organic polymers such as sulfur-containing polythiophene and polystyrene, natural polymers such as polysaccharides represented by cellulose, lignin, mannan, polygalactouronic acid, chitosan, and saccharose, thermoplastic resins such as polyphenylene sulfide and polyphenylene oxide, thermosetting resins such as furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin, and carbonaceous materials of these or carbonizable organic materials dissolved in a low molecular weight organic solvent such as benzene, toluene, xylene, quinoline, and n-hexane, and carbonaceous materials of these.
[0220] When the negative electrode composite contains a negative electrode active material containing a metal and a carbonaceous material, the mass ratio of the negative electrode active material containing a metal and the carbonaceous material is preferably 1 / 99 to 99 / 1, more preferably 5 / 95 to 95 / 5, and even more preferably 10 / 10 to 90 / 10.
[0221] When the composition of the present disclosure contains a negative electrode active material, the content of single-layer carbon nanotubes is preferably 0.001 to 10 parts by mass with respect to 100 parts by mass of the negative electrode active material.
[0222] When the composition of the present disclosure contains a negative electrode active material, the content of the binder is preferably 0.01 to 20.0 parts by mass per 100 parts by mass of the positive electrode active material.
[0223] The content of the electrode active material (positive electrode active material or negative electrode active material) is preferably 40 mass% or more in the composition to increase the capacity of the electrode obtained.
[0224] The above powder electrode material may also include a conductive agent. Examples of conductive agents include carbon blacks such as acetylene black and ketjen black, carbon materials such as graphite, carbon fibers, carbon nanotubes, carbon nanohorns, graphene, etc.
[0225] The ratio of the powder electrode material (active material and conductive agent) in the composition to the copolymer described above is typically about 80:20 to 99.5:0.5 by mass ratio, and is determined by considering the retention of the powder component, adhesion to the current collector, and conductivity of the electrode.
[0226] The composition may contain, for example, acrylic resins such as polyacrylic acid, polymethacrylate, and polymethyl methacrylate, polyimide, polyamide and polyamideimide resins, styrene rubber, butadiene rubber, styrene-butadiene rubber, etc.
[0227] To improve slurry stability, the composition may contain a dispersant such as a resin-based agent having a surfactant function, a cationic surfactant, or a nonionic surfactant.
[0228] The composition can be prepared by mixing a single-layer carbon nanotube, a binder, and a solvent. Powdered electrode materials may also be dispersed or mixed into the obtained composition. Then, the obtained composition is uniformly coated onto a current collector, such as a metal foil or metal mesh, dried, and, if necessary, pressed to form a thin layer of electrode material on the current collector, thereby forming a thin-film electrode. Alternatively, the composition may be prepared by first mixing the single-layer carbon nanotube, the binder, and the powdered electrode materials, and then adding a solvent.
[0229] (electrode)
[0230] The electrode of the present disclosure comprises a current collector and an electrode material layer. The electrode material layer is formed using the composition of the present disclosure and may be provided on one side of the current collector or on both sides. The electrode of the present disclosure may be a positive electrode having a positive electrode material layer or a negative electrode having a negative electrode material layer.
[0231] Since the electrode of the present disclosure has an electrode material layer formed using the composition of the present disclosure, by using the electrode of the present disclosure in a battery, a battery with excellent output characteristics, cycle characteristics, and 60°C storage characteristics, and a reduced gas generation rate can be obtained.
[0232] The density of the electrode material layer is preferably 2.0 to 5.0 g / cm³, and more preferably 2.5 to 4.5 g / cm³.
[0233] The density of the electrode material layer can be calculated from the mass and volume of the electrode material layer.
[0234] The thickness of the electrode material layer is preferably 20 μm or more, more preferably 30 μm or more, even more preferably 40 μm or more, particularly preferably 45 μm or more, preferably 170 μm or less, and more preferably 150 μm or less, in order to obtain even higher battery characteristics. In addition, the thickness of the electrode material layer may be 85 μm or less, or less than 69 μm.
[0235] The thickness of the electrode material layer can be measured by a micrometer. In the present disclosure, the thickness of the electrode material layer is the thickness per side when the electrode material layer is provided on both sides of the current collector.
[0236] As a current collector provided by the electrode of the present disclosure, examples include metal foils or metal meshes such as iron, stainless steel, copper, aluminum, nickel, and titanium, and among these, aluminum foil is preferred.
[0237] The electrode of the present disclosure can be suitably manufactured by a manufacturing method of applying the composition of the present disclosure to a current collector. After applying the composition, the coating film may also be dried, and the obtained dried coating film may be pressed.
[0238] The amount of the composition applied to the current collector is preferably 10 mg / cm² or more, more preferably 17.5 mg / cm² or more, preferably 60 mg / cm² or less, and more preferably 50 mg / cm² or less. The amount of the composition applied is the dry weight of the composition per unit area.
[0239] (Secondary battery)
[0240] In addition, according to the present disclosure, a secondary battery having the above electrode is provided.
[0241] The secondary battery of the present disclosure has an electrode formed using the composition of the present disclosure, so it has excellent output characteristics, cycle characteristics, and 60°C storage characteristics, and a low gas generation rate.
[0242] The secondary battery of the present disclosure comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte, and it is preferable that one or both of the positive electrode and the negative electrode are the electrodes. Additionally, the secondary battery of the present disclosure comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte, and it is preferable that the positive electrode is the electrode. Additionally, a separator may be interposed between the positive electrode and the negative electrode.
[0243] The non-aqueous electrolyte may use one or more of known solvents, such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethylmethyl carbonate, although it is not particularly limited. The electrolyte may also use any conventionally known one, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.
[0244] The electrode of the present disclosure is suitable for use as an electrode for a wound-type secondary battery in that it has excellent flexibility and conductivity, the current collector and the electrode material layer are sufficiently in close contact, and it can form a secondary battery with excellent battery characteristics. In addition, the secondary battery of the present disclosure may be a wound-type secondary battery.
[0245] The electrode of the present disclosure is for non-aqueous electrolyte secondary batteries and is useful not only for lithium-ion secondary batteries using the liquid electrolyte described above, but also for polymer electrolyte lithium secondary batteries. In addition, it is also useful for electric double layer capacitors.
[0246] Although embodiments have been described above, it will be understood that various changes in form or detail are possible without departing from the intent and scope of the patent claims.
[0247] Examples
[0248] The following describes embodiments of the present disclosure, but the present disclosure is not limited to these embodiments.
[0249] Each value of the example was measured by the following method.
[0250] (Ratio of VdF units to TFE units in fluorine-containing copolymers)
[0251] The ratio of VdF units to TFE units in the fluorine-containing copolymer was determined using an NMR analyzer (Agilent Technologies, VNS400MHz), 19 The polymer was measured in the DMF-d7 solution state using F-NMR.
[0252] 19 By measuring F-NMR, the areas of the following peaks (A, B, C, D) were determined, and the ratio of VdF units to TFE units was calculated.
[0253] A: Area of the peak between -86 ppm and -98 ppm
[0254] B: Area of the peak between -105 ppm and -118 ppm
[0255] C: Area of the peak between -119 ppm and -122 ppm
[0256] D: Area of the peak between -122 ppm and -126 ppm
[0257] Ratio of VdF units: (4A+2B) / (4A+3B+2C+2D)×100[mol%]
[0258] Ratio of TFE units: (B+2C+2D) / (4A+3B+2C+2D)×100[mol%]
[0259] (Weight-average molecular weight)
[0260] It was measured by gel permeation chromatography (GPC). Using a Dosoh HLC-8320GPC and a column (three SuperAWM-H connected in series), the weight-average molecular weight was calculated from the data measured by flowing dimethylformamide (DMF) as a solvent at a flow rate of 0.3 ml / min (reference: polystyrene).
[0261] (Melting point)
[0262] Using a differential scanning calorimetry (DSC) device, the temperature corresponding to the maximum value in the heat of fusion curve when the temperature was raised from 30°C to 220°C at a rate of 10°C / min, then lowered to 30°C at a rate of 10°C / min, and then raised again to 220°C at a rate of 10°C / min was determined as the melting point.
[0263] (viscosity)
[0264] The viscosity of the composition was measured using a Type B viscometer (Brookfield LV-DV2T) under conditions of 25°C, rotor No. SC4-21, and rotation speed of 20 rpm, and the measured value after 10 minutes from the start of measurement was taken as the viscosity.
[0265] In the examples and comparative examples, a polymer having the following properties was used as a binder.
[0266] Fluorine-containing copolymer (A): Fluorine-containing copolymer containing VdF units and TFE units
[0267] VdF / TFE=81 / 19(mol%)
[0268] Weight-average molecular weight 1,230,000
[0269] Melting point 128℃
[0270] PVdF(B): VdF homopolymer
[0271] Weight-average molecular weight 1,800,000
[0272] Melting point 171℃
[0273] In addition, in the examples and comparative examples, the following positive electrode active materials were used.
[0274] NMC811: LiNi0 . 8Mn0 . 1Co0 . 102
[0275] In addition, in the examples and comparative examples, the following single-layer carbon nanotubes were used.
[0276] Single-layer carbon nanotube (product name "TUBALL BATT SWCNT", manufactured by OCSiAl)
[0277] Average outer diameter: 1.6±0.4 nm
[0278] Length: 5㎛ or more
[0279] Average G / D ratio: 86.5±7.1
[0280] Example 1
[0281] (Preparation of composition)
[0282] A composition having the composition described in Table 1 was prepared by mixing a single-layer carbon nanotube, a fluorine-containing copolymer (A), and 3-methoxy-N,N-dimethylpropanamide. The viscosity of the obtained composition was measured. The results are shown in Table 1.
[0283] (Preparation of the Jeonggeuk combination)
[0284] The obtained composition and PVdF (B) were mixed such that the mass ratio of the fluorine-containing copolymer (A) to PVdF (B) was as described in Table 1. The obtained mixture, NMC811, acetylene black, and 3-methoxy-N,N-dimethylpropanamide were mixed to prepare a positive electrode composite with a solid content of 71 mass%. The composition of the obtained positive electrode composite is shown in Table 1.
[0285] (Production of a straight play)
[0286] The obtained positive electrode mixture was uniformly coated on one side of a positive electrode current collector (aluminum foil with a thickness of 20 μm), and dried at 120°C for 60 minutes to completely volatilize 3-methoxy-N,N-dimethylpropanamide. Then, a positive electrode having a positive electrode material layer and a positive electrode current collector was produced by applying a pressure of 10 t using a roll press machine and pressing.
[0287] (Production of the play)
[0288] Artificial graphite powder was used as the negative electrode active material, an aqueous emulsion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose 1 mass%) as the thickener, and an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber 50 mass%) as the binder. The active material, thickener, and binder were mixed in an aqueous medium with a solid ratio of 97.6 / 1.2 / 1.2 (mass ratio) to prepare a negative electrode composite slurry. The negative electrode composite slurry was uniformly coated onto a copper foil with a thickness of 20 μm, dried, and then compression-molded using a press machine to form a negative electrode.
[0289] (Production of lithium-ion secondary batteries)
[0290] A battery element was fabricated by stacking a positive electrode, a negative electrode, and a polyethylene separator in the order of negative electrode, separator, and positive electrode.
[0291] This battery element was inserted into a pouch containing a laminate film in which both sides of an aluminum sheet (thickness 40 μm) were coated with a resin layer, with the positive and negative terminals protruding. Subsequently, 1.2 g of an electrolyte (LiPF6 dissolved at a concentration of 1 mol / liter in a solvent mixed with ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3 / 7, and 2 mass% of vinylene carbonate added) was injected into each pouch, and vacuum sealing was performed to produce a sheet-shaped lithium-ion secondary battery.
[0292] (Output characteristics)
[0293] The lithium-ion secondary battery prepared above was charged to 4.2V at 25°C with a current equivalent to 0.2C (hereinafter referred to as CC / CV charging) (0.1C cut-off), then discharged to 3V with a constant current of 0.2C, and the initial discharge capacity was calculated from the discharge capacity of the third cycle. Here, 1.0C represents the current value for discharging the battery's reference capacity in one hour, and for example, 0.2C represents one-fifth of that current value. The battery, for which the evaluation of the initial discharge capacity was completed, was charged at 25°C with a constant current of 0.2C and then discharged to 3V with a constant current of 5.0C. The ratio of the discharge capacity at 5.0C to the initial discharge capacity was calculated and this was set as the discharge capacity ratio (%) at 5.0C.
[0294] (5.0C discharge capacity) ÷ (0.2C initial discharge capacity) × 100 = 5.0C discharge capacity ratio (%)
[0295] The result of calculating the value of Comparative Example 1 as 100 is shown in Table 1.
[0296] (Cycle characteristics)
[0297] The lithium-ion secondary battery prepared above was charged to 4.2V at 25°C with a current equivalent to 1.0C (0.1C cut-off), then discharged to 3V with a constant current of 1.0C, and this was considered one cycle. The initial discharge capacity was calculated from the discharge capacity. The cycle was performed again, and the discharge capacity after 300 cycles was measured. The ratio of the discharge capacity after 300 cycles to the initial discharge capacity was calculated, and this was set as the capacity retention rate (%).
[0298] (Discharge capacity after 300 cycles) ÷ (Initial discharge capacity at 1.0C) × 100 = Capacity retention rate (%)
[0299] The result of calculating the value of Comparative Example 1 as 100 is shown in Table 1.
[0300] (60℃ storage characteristics)
[0301] After the evaluation of the initial discharge capacity was completed, the battery was charged again to 4.2V using CC / CV charging (0.1C cut-off) and then stored at a high temperature of 60°C for 7 days. Next, it was discharged to 3V at 0.2C at 25°C, and the remaining capacity after high temperature storage was measured. The ratio of the remaining capacity to the initial discharge capacity was calculated and set as the retention capacity retention rate (%).
[0302] (Remaining capacity) ÷ (Initial discharge capacity) × 100 = Retention capacity retention rate (%)
[0303] The result of calculating the value of Comparative Example 1 as 100 is shown in Table 1.
[0304] (Gas generation rate)
[0305] After the evaluation of the initial discharge capacity was completed, the battery was charged again to 4.2V using CC / CV charging (0.1C cut-off), and then stored at a high temperature of 60°C for 7 days. After cooling the battery sufficiently, the volume of the battery was measured by the Archimedes method, and the gas generation rate was calculated from the volume change before and after the high temperature storage.
[0306] Gas generation rate (%) = (Volume after high-temperature storage (ml)) / (Volume before high-temperature storage (ml)) × 100
[0307] The result of calculating the value of Comparative Example 1 as 100 is shown in Table 1.
[0308] Examples 2 to 4, Comparative Examples 1 to 2
[0309] A composition was prepared in the same manner as in Example 1, except that the type and amount of binder and the type of solvent were changed as described in Table 1, and the viscosity of the obtained composition was measured. The results are shown in Table 1.
[0310] In addition, a positive electrode composite was prepared and a positive electrode was manufactured in the same manner as in Example 1, except that the composition prepared in the examples and comparative examples was used, and the results were evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0311]
[0312] Example 5
[0313] (Preparation of composition)
[0314] A composition having the composition described in Table 2 was prepared by mixing a single-layer carbon nanotube, a fluorine-containing copolymer (A), and 3-methoxy-N,N-dimethylpropanamide. The viscosity of the obtained composition was measured. The results are shown in Table 2.
[0315] (Preparation of negative polarity combination)
[0316] The obtained composition and PVdF (B) were mixed such that the mass ratio of the fluorine-containing copolymer (A) to PVdF (B) was as described in Table 2. The obtained mixture, graphite powder, and 3-methoxy-N,N-dimethylpropanamide were mixed to prepare a negative electrode composite. The composition of the obtained negative electrode composite is shown in Table 2.
[0317] (Fabrication of a negative electrode having a negative electrode material layer)
[0318] The obtained negative electrode composite was applied to one side of a negative electrode current collector containing copper foil and dried. This was cut into a predetermined electrode size and rolled using a roll press to produce a negative electrode having a negative electrode material layer and a negative electrode current collector.
[0319] (Production of a straight play)
[0320] LiNi0 in positive electrode active material . 8Mn0 . 1Co0 .A positive electrode composite having a solid content of 71 mass% was prepared by mixing 97 mass parts of 1O2 (NMC811), 1.5 mass parts of acetylene black (AB) as a conductive aid, and 1.5 mass parts of an 8 mass% NMP solution of PVDF (B) as a binder. The obtained positive electrode composite was uniformly coated on one side of a positive electrode current collector (aluminum foil with a thickness of 20 μm) and dried at 120°C for 60 minutes to completely volatilize N-methyl-2-pyrrolidone, and then a positive electrode having a positive electrode material layer and a positive electrode current collector was produced by applying a pressure of 10 t using a roll press machine and pressing.
[0321] (Production of lithium-ion secondary batteries)
[0322] A battery element was fabricated by stacking a positive electrode, a negative electrode, and a polyethylene separator in the order of negative electrode, separator, and positive electrode.
[0323] This battery element was inserted into a pouch containing a laminate film in which both sides of an aluminum sheet (thickness 40 μm) were coated with a resin layer, with the positive and negative terminals protruding. Subsequently, 1.2 g of an electrolyte (LiPF6 dissolved at a concentration of 1 mol / liter in a solvent mixed with ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3 / 7, and 2 mass% of vinylene carbonate added) was injected into each pouch, and vacuum sealing was performed to produce a sheet-shaped lithium-ion secondary battery.
[0324] (Measurement of battery characteristics)
[0325] For the lithium-ion secondary battery prepared above, output characteristics, cycle characteristics, 60°C storage characteristics, and gas generation rate were evaluated in the same manner as in Example 1. The results calculated by setting the value of Comparative Example 3 to 100 are shown in Table 2.
[0326] Examples 6 to 10, Comparative Examples 3 to 5
[0327] A composition was prepared in the same manner as in Example 5, except that the type and amount of binder and the type of solvent were changed as described in Table 2, and the viscosity of the obtained composition was measured. The results are shown in Table 2.
[0328] In addition, a negative electrode composite was prepared and a negative electrode was manufactured in the same manner as in Example 5, except that the composition prepared in the example and comparative example was used, and the evaluation was performed in the same manner as in Example 5. The results calculated with the value of Comparative Example 3 as 100 are shown in Table 2.
[0329]
Claims
Claim 1 A composition comprising a single-layer carbon nanotube, a binder, and a solvent, wherein the solvent is at least one selected from the group consisting of a solvent represented by general formula (1b-1) and a solvent represented by general formula (1b-2), and the binder is a composition comprising a fluorine-containing polymer containing vinylidene fluoride units. General formula (1b-1): (during food, R 1b is an alkyl group, an alkoxyalkyl group, an acylalkyl group, an alkenyl group, an amino group, or an aminoalkyl group, and R 2b and R 3b is independently an alkyl group or an alkoxyalkyl group, and R 1b , R 2b and R 3b The total number of carbon atoms is 5 or more. R 2b and R 3b is, combined with each other, R 2b and R 3b It may form a ring with the nitrogen atom to which it bonds, or it may include an oxygen atom as a constituent atom of the ring.) General formula (1b-2): (In the formula, ring A is a 5- or 6-won amide ring, and R 4b is an alkyl group having 3 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an alkenyl group, and ring A and R 4b The total number of carbon atoms is 5 or more.) Claim 2 A composition according to claim 1, wherein the solvent is at least one selected from the group consisting of 3-methoxy-N,N-dimethylpropanamide and N-butyl-2-pyrrolidone. Claim 3 A composition according to claim 1 or 2, wherein the average outer diameter of the single-layer carbon nanotube is 2.5 nm or less. Claim 4 A composition according to claim 1 or 2, wherein the average G / D ratio of the single-layer carbon nanotube is 2 or higher. Claim 5 A composition according to claim 1 or 2, wherein the binder is a fluorine-containing polymer containing polyvinylidene fluoride. Claim 6 A composition according to claim 1 or 2, wherein the binder is a fluorine-containing copolymer containing vinylidene fluoride units and monomer units other than vinylidene fluoride, as the fluorine-containing polymer. Claim 7 A composition in which, in claim 6, the other monomer is a fluorinated monomer (except vinylidene fluoride). Claim 8 A composition according to claim 6, wherein the other monomer is at least one selected from the group consisting of tetrafluoroethylene, chlorotrifluoroethylene, (meth)acrylic acid, 2,3,3,3-tetrafluoropropene, hexafluoropropylene, and fluoroalkyl vinyl ether. Claim 9 A composition according to claim 6, wherein the binder comprises, as the fluorine-containing polymer, polyvinylidene fluoride and a fluorine-containing copolymer containing vinylidene fluoride units and monomer units other than vinylidene fluoride. Claim 10 A composition according to claim 9, wherein the mass ratio of the polyvinylidene fluoride to the fluorine-containing copolymer (polyvinylidene fluoride / fluorine-containing polymer) is 99 / 1 to 1 / 99. Claim 11 A composition used to form an electrode of an electrochemical device, in accordance with claim 1 or 2. Claim 12 A composition according to claim 1 or 2, further comprising a powder electrode material (except for the single-layer carbon nanotube). Claim 13 In claim 12, the above powder electrode material is a composition containing a lithium composite oxide as a positive electrode active material. Claim 14 A composition according to claim 12, wherein the above-mentioned powder electrode material contains a negative electrode active material that exhibits a potential of 2.5V or less based on Li when alloyed with Li or combined with Li. Claim 15 An electrode comprising a current collector and an electrode material layer formed by a composition described in claim 1 or 2, provided on one or both sides of the current collector. Claim 16 A secondary battery having the electrodes described in paragraph 15. Claim 17 delete Claim 18 delete
Citation Information
Patent Citations
High-energy-density lithium-ion battery and preparation method thereof
CN107394202A
Composition for electrochemical device, positive electrode mixture, positive electrode structure, and secondary battery
WO2021002369A1
